Middle Miocene short-lived Tethyan seaway through the Zagros foreland basin: Facies analysis and paleoenvironmental reconstruction of mixed siliciclastic-carbonate deposits of Mishan Formation, Dezful Embayment, SW Iran. (June 2022) - Mohammadkhani, Hossein; Hosseini-Barzi, Mahboubeh; Sadeghi, Abbas; Pomar, Luis
Abstract: Integrated sedimentological and petrographical analyses have been used for paleo-environmental reconstruction of mixed siliciclastic-carbonate deposits of Mishan Formation (late Burdigalian-Serravallian) in the Dezful Embayment within the Zagros foreland basin. The carbonate deposits alternated with marl layers consisting of open marine, restricted to semi-restricted subtidal lagoon and tide-related facies associations with organic buildups deposited within tropical to subtropical warm water multi-factory platform including euphotic and meso-oligophotic factories. The siliciclastic deposits comprise progradational tide-influenced delta deposits including prodelta, delta front and delta plain facies associations. The lack of wave related structures and the absence of the shelf type evidence together with tide-related deposits within the carbonate facies and prograding delta deposits indicate a tide-dominated mixed siliciclastic-carbonate homoclinal ramp with the development of organic buildups. These sediments deposited within the short-lived Tethyan seaway resulted from Middle Miocene Climate Optimum through the Zagros foreland basin. Predominant heterozoan skeletal grains and alternation of marl layers with carbonate sediments indicate high nutrient and sediment flux from adjacent highlands. Carbonate tidal deposits within the siliciclastic sediments suggest that the tidal currents have provided suitable ecological conditions for carbonate production by supplying nutrients for heterotrophic organisms and pumping clear water from the ocean. Shallowing upward trend from marine carbonates and marls to prograding siliciclastic paralic and non-marine deposits of the Mishan Formation within the studied area can be linked to the eustatic sea-level fall in response to the Middle Miocene Climate Transition which led to the closure of Tethyan seaway in the Dezful Embayment. Highlights: The Zagros foreland basin connected the Indian Ocean and proto-Mediterranean Sea during the Middle Miocene Climate Optimum. During the late Burdigalian-Serravallian, a mixed siliciclastic-carbonate homoclinal ramp developed in the Dezful Embayment. The carbonate deposition of the Mishan Formation occurred in the euphotic and the meso-oligophotic carbonate factories. E-Antarctica ice-sheet expansion (MMCT) led to marine regression and stepwise closure of Neotethys seaway.